Progressive dyspnoea in a patient with idiopathic non-cirrhotic portal hypertension. Issue 1 (8th March 2022) - Cullivan, Sarah; McCullagh, Brian; Gaine, Sean
This case of progressive dyspnoea in a 43-year-old with idiopathic non-cirrhotic portal hypertension highlights important pulmonary vascular complications of chronic liver disease https://bit.ly/3rwEkhP